IRAQ'S CONSUMER SPENDING AFTER 2003: FACTS AND INDICATORS - Prof. Dr. Souad Qassim Al-Moussawi (Scholar Express Journals, 2022)
Household consumer spending is deemed as one of the main determinants of building national income, as it represents a large percentage of total expenditure in many countries of the world, in addition, it plays a significant role in the economy's entertainment and growth, as it is one of the most important components of aggregate demand, which has earned it a d and pivotal importance in countries' economies and making it an essential field, in which many pieces of research reached scientific facts that serve the decision
Keywords: Household consume; private consumption; economic globalization; luxury consumption